2013
DOI: 10.1308/003588413x13629960045715
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy and cost effectiveness of intraoperative cell salvage in pelvic trauma surgery

Abstract: INTRODUCTION Pelvic acetabular injuries are associated with significant blood loss. This is compounded by multiple surgical interventions including definitive fracture fixation, which put patients at further risk of postoperative transfusion. We use intraoperative cell salvage routinely as a blood conservation strategy to address this issue. This is a prospective evaluation of the clinical efficacy and cost effectiveness of using intraoperative cell salvage in patients with pelvic acetabular injuries. METHODS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 25 publications
3
32
0
Order By: Relevance
“…Although the influence of CS use on perioperative transfusion requirements in patients undergoing PAO has not previously been addressed, our results are in concordance with multiple previous studies of patients undergoing comparable orthopedic procedures, such as revision hip arthroplasty [33, 34] and acetabular fracture fixation [35, 36]. A Cochrane review of 21 randomized, controlled trials by Carless et al .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Although the influence of CS use on perioperative transfusion requirements in patients undergoing PAO has not previously been addressed, our results are in concordance with multiple previous studies of patients undergoing comparable orthopedic procedures, such as revision hip arthroplasty [33, 34] and acetabular fracture fixation [35, 36]. A Cochrane review of 21 randomized, controlled trials by Carless et al .…”
Section: Discussionsupporting
confidence: 91%
“…Odak et al . [35] presented their prospective review of 30 patients undergoing pelvic acetabular fracture fixation. In their study population, 47% required allogenic blood transfusion, and a statistically significant inverse relationship existed between volume of CS transfusion and postoperative allogenic transfusion requirement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It concluded that CS in this setting reduces blood transfusion and is cost effective. Prospective data for 30 patients undergoing pelvic acetabular fracture fixation found a mean blood loss of 1233 ml and an average of 388 ml retransfused through CS; only 47% of patients required allogeneic transfusion. In a combat hospital, a CS feasibility study concluded that CS was most successful in patients with gunshot wounds and cavity injuries compared with limb or blast injuries .…”
Section: Orthopaedics and Traumamentioning
confidence: 99%
“…Studies on the intraoperative transfusion strategies during orthopaedic xation surgeries were mostly about autologous blood transfusion and its outcome [7,8], the impact of the intraoperative allogeneic blood transfusion on de nitive stabilization surgeries of pelvic fracture patients has not been discussed and still remains unclear. Multiple factors can affect the intraoperative blood transfusion, such as the coagulation function, the estimated blood loss, the type of surgery, and the traumatic condition.…”
Section: Introductionmentioning
confidence: 99%